2015
DOI: 10.3389/fpls.2015.00321
|View full text |Cite
|
Sign up to set email alerts
|

Growth, physiological, and biochemical responses of Camptotheca acuminata seedlings to different light environments

Abstract: Light intensity critically affects plant growth. Camptotheca acuminata is a light-demanding species, but its optimum light intensity is not known. To investigate the response of C. acuminata seedlings to different light intensities, specifically 100% irradiance (PAR, 1500 ± 30 μmol m−2 s−1), 75% irradiance, 50% irradiance, and 25% irradiance, a pot experiment was conducted to analyze growth parameters, photosynthetic pigments, gas exchange, chlorophyll fluorescence, stomatal structure and density, chloroplast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 40 publications
7
25
0
1
Order By: Relevance
“…In this study, changes in biomass accumulation in plants grown under varying light quality were closely linked to Chl contents and gas-exchange attributes. It has been revealed that RL plays a significant role in the photosynthetic apparatus development and affects morphogenesis by light-induced transformations of phytochrome system (Ma et al 2015a). Light energy absorbed by Chl molecules can undergo three fates: (1) used to drive photosynthesis, (2) dissipated as heat (nonphotochemical quenching), or (3) reemitted as Chl fluorescence (Maxwell and Johnson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, changes in biomass accumulation in plants grown under varying light quality were closely linked to Chl contents and gas-exchange attributes. It has been revealed that RL plays a significant role in the photosynthetic apparatus development and affects morphogenesis by light-induced transformations of phytochrome system (Ma et al 2015a). Light energy absorbed by Chl molecules can undergo three fates: (1) used to drive photosynthesis, (2) dissipated as heat (nonphotochemical quenching), or (3) reemitted as Chl fluorescence (Maxwell and Johnson 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis is determined by chlorophyll (Chl) content and the flux of energy in leaves. Plants should adjust Chl (a+b) content and Chl a/b ratio to adapt to certain environmental conditions and optimize photosynthesis under high and low irradiance (Ma et al 2015). Liming (material contains calcium and/or magnesium compounds capable of neutralizing soil acidity) and P fertilization treatments, just as in other silvicultural treatments, in turn, can reduce the high-light stress effects on chloroplast pigments and stimulate photosynthesis in high light plasticity plants (Filstrup andDowning 2017, Lopes et al 2019) after thinning, due to the enhancement of the nutrient uptake of trees and the availability of nutrients in soil, mainly calcium (Ca), magnesium (Mg), and P. On the other hand, under conditions, where light is limited, liming can increase leaf Chl (due to the increase of Mg concentrations in leaves and P addition) in order to favor increased light energy flux and use (Filstrup and Downing 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Light is considered the most direct environmental factor affecting plant growth and development ( Ma et al, 2015 ; Yamori, 2016 ). Specifically, changes in light wavelengths due to the different properties of light-harvesting pigments can directly affect plant morphological, anatomical, biochemical, and physiological parameters ( Haliapas et al, 2008 ; Fan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%